Determination of Binary Interaction Parameters for Ternary Polymer–Polymer–Solvent Systems Using Raman Spectroscopy. Issue 2 (4th June 2020) - Gracia‐Medrano‐Bravo, Víctor‐Alfonso; Merklein, Lisa; Oberle, Nikolas; Batora, Manuel; Scharfer, Philip; Schabel, Wilhelm
Abstract: Multilayer coatings and drying of polymer films are widely used to produce different applications like organic electronics or barrier foils. If the product quality requires separated layers, partial or immiscible systems can be used to avoid interdiffusion between the layers. For the prediction of a possible phase separation of a ternary polymer–polymer–solvent system, it is required to measure or obtain from a data bank the three binary interaction parameters of the system to describe its thermodynamic behavior. This poses a challenge due to the scarce data and measurement techniques for polymer–solvent interaction parameters, but even more for polymer–polymer interaction parameters. In this work, a numerical routine is developed to predict the phase separation for given interaction parameters and is validated with literature results. Subsequently, different ternary polystyrene–poly(methyl methacrylate)–toluene mixtures are prepared and the resulting composition of the phase (or phases) is measured via Raman spectroscopy. The determined equilibrium data are used to fit the binary interaction parameters, which can be used afterward as input parameters for the numerical routine in order to predict the ternary phase diagram of the system. Abstract : A routine is developed to predict the phase separation of ternary polymer–polymer–solvent systems. In addition, equilibrium data of polystyrene–poly(methyl methacrylate)–toluene mixtures are measured via Raman spectroscopy and used to determine interaction parameters. The calculated phase diagram shows a good agreement with the experiments.